The Expression of Epstein-Barr virus in Breast cancer in relation to age - Hanna, Ban Jamal; Habib, Manal Adnan; Al-Mosawi, Huda Adnan (AL-Kindy College Medical Journal, 2011)
Background: Breast cancer is the most common malignancy affecting females worldwide. The association of Epstein-Barr virus (EBV) with this cancer is a longstanding interest to this field. Aim: to investigate the presence of EBV in breast tumor tissue in relation to age. Patients and Methods: Paraffin-embedded tissue blocks from 45 female patients with breast tumors (ranged in age from 28 to 85 years) were retrieved. The cases were grouped into two categories: group (A): included 30 cases with breast carcinoma and group (B): included 15 cases with benign breast diseases as a control group .The expression of EBV protein was examined immunohistochemically. Results: Twelve (40%) of the 30 breast cancer cases (group A) were reported as positive for EBV expression and significantly higher in patients less than 40 years age (P= 0.026). Conclusion: the results of the current study might refer to the significance of EBV expression in breast tissue of young patients with breast cancer.